Dietary intervention with green dwarf banana flour (Musa sp. AAA) modulates oxidative stress and colonic SCFAs production in the TNBS model of intestinal inflammation - Almeida-Junior, L. D. [UNESP]; Curimbaba, T. F.S. [UNESP]; Chagas, A. S. [UNESP]; Quaglio, A. E.V. [UNESP]; Di Stasi, L. C. [UNESP] (Elsevier, 2017)
Dietary products with prebiotic properties have been used to promote protective effects during inflammatory process. Prebiotics are source of short chain fatty acids (SCFAs) that have been associated with anti-inflammatory effects. Banana (Musa sp. AAA) is rich in resistant starch, which is used by colonic microbiota to SCFAs production. For this, we used the trinitrobenzenesulphonic acid model of intestinal inflammation to evaluate whether intestinal anti-inflammatory effect is related to prebiotic effects. Dietary intervention with green dwarf banana flour (5% or 10%) increased acetate, propionate and butyrate concentration. The protective effects was also evidenced by reduction in extension of lesion, inhibition of myeloperoxidase activity, prevention in glutathione depletion, increased mucin production and mucosal healing. This way, dietary green dwarf banana modulates oxidative stress and colonic production of SCFAs increasing intestinal tissue protection and may be used as a complementary product to prevent or avoid relapse of symptoms in inflammatory bowel diseases.
Keywords: Acetate; Banana; Butyrate; Inflammatory Bowel Disease (IBD); Musa sp. AAA; Propionate; Short Chain Fatty Acids (SCFA)